N‐ethyl‐N‐nitrosourea–Induced Adaptor Protein 2 Sigma Subunit 1 (Ap2s1) Mutations Establish Ap2s1 Loss‐of‐Function Mice. (2nd May 2017) - Gorvin, Caroline M; Rogers, Angela; Stewart, Michelle; Paudyal, Anju; Hough, Tertius A; Teboul, Lydia; Wells, Sara; Brown, Steve DM; Cox, Roger D; Thakker, Rajesh V
ABSTRACT: The adaptor protein‐2 sigma subunit (AP2σ), encoded by AP2S1, forms a heterotetrameric complex, with AP2α, AP2β, and AP2μ subunits, that is pivotal for clathrin‐mediated endocytosis, and AP2σ loss‐of‐function mutations impair internalization of the calcium‐sensing receptor (CaSR), a G‐protein–coupled receptor, and cause familial hypocalciuric hypercalcemia type‐3 (FHH3). Mice with AP2σ mutations that would facilitate investigations of the in vivo role of AP2σ, are not available, and we therefore embarked on establishing such mice. We screened >10, 000 mice treated with the mutagen N‐ethyl‐N‐nitrosourea (ENU) for Ap2s1 mutations and identified 5 Ap2s1 variants, comprising 2 missense (Tyr20Asn and Ile123Asn) and 3 intronic base substitutions, one of which altered the invariant donor splice site dinucleotide gt to gc . Three‐dimensional modeling and cellular expression of the missense Ap2s1 variants did not reveal them to alter AP2σ structure or CaSR‐mediated signaling, but investigation of the donor splice site variant revealed it to result in an in‐frame deletion of 17 evolutionarily conserved amino acids (del17) that formed part of the AP2σ α1‐helix, α1‐β3 loop, and β3 strand. Heterozygous mutant mice ( Ap2s1 +/del17 ) were therefore established, and these had AP2σ haplosufficiency but were viable with normal appearance and growth. Ap2s1 +/del17 mice, when compared with Ap2s1 +/+ mice, also had normal plasma concentrations of calcium, phosphate, magnesium, creatinine, urea, sodium, potassium, and alkaline phosphatase activity; normal urinary fractional excretion of calcium, phosphate, sodium, and potassium; and normal plasma parathyroid hormone (PTH) and 1, 25‐dihydroxyvitamin D (1, 25(OH)2 ) concentrations. However, homozygous Ap2s1 del17 /del 17 mice were non‐viable and died between embryonic days 3.5 and 9.5 (E3.5–9.5), thereby indicating that AP2σ likely has important roles at the embryonic patterning stages and organogenesis of the heart, thyroid, liver, gut, lungs, pancreas, and neural systems. Thus, our studies have established a mutant mouse model that is haplosufficient for AP2σ. © 2017 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.